2017
DOI: 10.3389/fneur.2017.00338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transcranial Magnetic Stimulation on Functional Movement Disorders: Cortical Modulation or a Behavioral Effect?

Abstract: IntroductionRecent studies suggest that repeated transcranial magnetic stimulation (TMS) improves functional movement disorders (FMDs), but the underlying mechanisms are unclear. The objective was to determine whether the beneficial action of TMS in patients with FMDs is due to cortical neuromodulation or rather to a cognitive-behavioral effect.MethodConsecutive patients with FMDs underwent repeated low-frequency (0.25 Hz) magnetic stimulation over the cortex contralateral to the symptoms or over the spinal ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…Our hypothesis predicted that if rTMS exerts its effect mainly through a cognitive-behavioral-suggestion mechanism, as previously argued, 17,22 we would not find any differences in outcome measures between the real rTMS and control groups. Moreover, given that there is no evidence that placebo interventions have a long-term benefit, any placebo-induced decrease in tremor would probably be transient, 23 as 42% and 57% of the patients included in the 2 consecutive studies by Garcin and colleagues 17,22 relapsed during follow-up. By contrast, any longer lasting changes induced by a real rTMS intervention applied with suitable parameters able to induce excitability changes would be prolonged by using hypnosis as an add-on therapy.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…Our hypothesis predicted that if rTMS exerts its effect mainly through a cognitive-behavioral-suggestion mechanism, as previously argued, 17,22 we would not find any differences in outcome measures between the real rTMS and control groups. Moreover, given that there is no evidence that placebo interventions have a long-term benefit, any placebo-induced decrease in tremor would probably be transient, 23 as 42% and 57% of the patients included in the 2 consecutive studies by Garcin and colleagues 17,22 relapsed during follow-up. By contrast, any longer lasting changes induced by a real rTMS intervention applied with suitable parameters able to induce excitability changes would be prolonged by using hypnosis as an add-on therapy.…”
supporting
confidence: 63%
“…In all of these studies, TMS was instead used as a suggestive tool to induce a nonspecific cognitive-behavioral effect that was clearly demonstrated by Garcin and colleagues. 22 The benefit induced by the first intervention was maintained across the study's time course in almost all of the patients in the active group, whereas only 1 patient in the control group had an improved Tremor subscore at M12 when compared with baseline, and 2 of them had worse PMDRS or Tremor subscores at M6 and or M12 when compared with baseline. These poor M6 to M12 results for the control group were unexpected given the encouraging results described in previous uncontrolled studies using single suprathreshold rTMS sessions to improve FMD.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Proposed therapeutic mechanisms of neurostimulation for FND include neuromodulation, placebo, and cognitive behavioral effects . A recent study comparing cortical to spinal root stimulation favored the latter, but did not assess neurophysiological measures . Previous research has also shown that FND patients may have abnormal suppression of cortical excitability during movement imagination tasks .…”
mentioning
confidence: 99%